Development, assessment and implementation of a novel FRP composite girder bridge. (18th July 2022) - Davids, William G.; Diba, Anthony; Dagher, Habib J.; Guzzi, Dante; Schanck, Andrew P.
Highlights: New FRP composite girder developed for short and medium-span highway bridge applications. Composite girder is lightweight, durable, and direct replacement for steel or concrete girders. Heavily instrumented FPR girder tested to assess bending behavior. New FRP girder-to-concrete-deck shear connector developed, tested for fatigue and strength resistance. Field implementation of 22.9-m span bridge described along with results of field load tests. Abstract: A lightweight, easily erected, hybrid glass-carbon FRP bridge girder is developed and assessed. A four-point bend test of a 12.45 m-span specimen is performed to assess load–deflection response, flexural strains and girder-concrete composite action. Web buckling occurred near peak load, but maximum measured bottom flange tensile strain reached more than 90% of its expected ultimate value. Strength and fatigue resistance of the girder-to-deck shear connection is experimentally assessed. Live-load testing of a new, 22.9 m-span bridge using these girders is performed. The test results verify the viability of this FRP girder for short- and medium-span bridges.